Earthflow reactivation assessment by multichannel analysis of surface waves and electrical resistivity tomography: A case study - El-Raouf Amr Abd; Iqbal Ibrar; Meister Julia; Abdelrahman Kamal; Alzahrani Hassan; Badran Osman M. (Open Geosciences, 2021)
In this study, we investigated the stability and reactivation of preexisting Tonghua landslide deposits in China, including the adjacent stable slope. We used an integrated approach, combining a multichannel analysis of surface waves (MASW) and electrical resistivity tomography (ERT). We used ERT to determine groundwater seepage paths, weathering conditions, water content, and the depth to bedrock. High-resolution two-dimensional (2D) shear-wave velocity MASW images, on the other hand, played an essential role in detecting both horizontal and vertical compositions, disjointedness, and sliding surfaces related to lithological borders. Based on seismic models, we considered four geological layers encountered in the stable slope, including fractured (gravel) and weathered (phyllite) materials, as a sliding mass. We combined the 2D resistivity profiles obtained to create pseudo-three-dimensional ERT images to estimate water-saturated and unsaturated masses. From the tomography results, we identified different preexisting deposits, including buried arable clay deposits, old accumulated earthflow deposits, a water accumulation zone, and a fissure runoff. Based on the resistivity results, the bottom of the earthflow deposits is susceptible to water, and oversaturation can reactivate the earthflow.